Some Remarks on the Russian Aggression against Ukraine in the context of the United Nations System of Maintenance of International Peace and Security - Perisic, Petra; Tomljenovic, Marija (Acta Universitatis Danubius. Juridica, 2023)
The paper observes the Russian aggression against Ukraine in the context of the United Nations system of maintenance of international peace and security, analyzing both the functionality of the UN bodies in performing their functions under the UN Charter, as well as observing the conflict in light of the UN Charter provisions on the use of force and self-defense, and in light of some other possible grounds for the use of force, not provided by the UN Charter. The paper demonstrates how the persistent problem of the Security Council deadlock, which manifested itself also in the case of the Russian aggression on Ukraine, has led to the General Assembly assuming the primary role in maintenance of international peace and security. The Ukrainian crisis has thus revived the debate on the long-awaited structural reform of the United Nations, but also on the revisiting the existing rules on the use of force, primarily the right to self-defense, which is too easily being used by states as a pretext for their unlawful actions.